A Channel Sounding System for Highly Interfered License-Exempt Frequency Bands - Robert, Jörg; Ghany, Ahmed Abdel; Rauh, Sebastian; Heuberger, Albert (Smart SysTech 2018; European Conference on Smart Objects, Systems and Technologies, 2018)
The Internet of Things (IoT) requires connectivity everywhere. An interesting solution to achieve this aim are Low Power Wide Area Networks (LPWAN). Tiny devices with transmit powers of 10 mW are able to transmit sensor data over distances of several kilometers in license-exempt frequency bands. The planning of LPWAN requires suitable channel models, which are currently not available. Hence, extensive channel measurements are required. However, the lack of free unused spectrum for channel sounding close to the typical LPWAN frequency bands requires the use of the license-exempt bands also for the channel sounding. As these bands are also used by other communication systems, significant levels of interference can be expected practically everywhere. Consequently, we developed a channel sounding system based on a software-defined radio approach that is able to provide accurate channel sounding results even in highly interfered license-exempt channels. We present different candidate algorithms that may be suitable to obtain the required robustness and compared them using simulation results. The results show that precise channel sounding is achievable in densely occupied license-exempt channels.

Decoding Performance in Low-Power Wide Area Networks With Packet Collisions - Lieske, Hendrik; Kilian, Gerd; Breiling, Marco; Rauh, Sebastian; Robert, Jörg; Heuberger, Albert (IEEE Transactions on Wireless Communications, 2016)
This paper proposes an analytical framework for the prediction of decoding error probabilities in heterogeneous wireless environments, where transmissions from various radio nodes with distinct Poisson-arrival rates and packet lengths populate the channel. Random channel access without feedback is assumed, where partial packet collisions can lead to the loss of packets. The analysis is based on the modeling of the collision length distribution between competing nodes. With recent results from information theory in the finite block length regime, we provide bounds on achievable decoding error probabilities for a given interference scenario. The new framework enables jointly considering inter-and intra-system interference, which is an important aspect in unlicensed radio bands. The framework's applicability to optimize system designs is demonstrated for a typical low-power wide area network scenario. We study the tradeoff between reliability and code rate for a point-to-point link and present achievable throughput regions. The analysis reveals the superior performance of coded time-hopping spread spectrum systems. They reach very low error probability even under strong interference for wide ranges of practically relevant load regions.
Keywords: Wireless sensor networks; interference; multi-user channels; channel coding; throughput

Empirical Study on Implicit Polarization Diversity and Space Diversity for Short Range Indoor-to-Outdoor Radio Links below 1GHz - Rauh, Sebastian; Lauterbach, Thomas; Lieske, Hendrik; Kilian, Gerd; Robert, Jörg; Heuberger, Albert (Smart SysTech 2017; European Conference on Smart Objects, Systems and Technologies; Proceedings of, 2017)
To assess the properties of short-range indoor-tooutdoor radio channels for applications like telemetry and smart metering we performed several field trials. They were operated in urban and commercial areas for several weeks each. Multiantenna receivers were used to record signal levels from two different antennas in parallel. Due to multipath propagation, in some of the channels low signal levels were observed. We therefore investigated if diversity techniques can be applied to improve reception, focussing on implicit polarization diversity and space diversity. From measurements over long time periods we derived the distributions of correlation coefficients and signal levels obtained from more than 80 radio links each using 3, 7 and 27 channels in the 169 MHz, 434 MHz and 868 MHz bands, respectively. For implicit polarization diversity and space diversity with horizontal spacing of antennas of one to six wavelengths we find the signals from the two antennas to be sufficiently decorrelated (correlation coefficents < 0.7) for most of the radio links and channels. In contrast, for space diversity with two antennas placed on the same mast at different heights, in many cases the signals were not sufficiently decorrelated. With respect to cross-polarization imbalance, we find values between -3 dB and 9 dB in the different trials and in the different frequency bands. The results show that generally both diversity schemes have the potential to significantly improve the performance of short range indoor-to-outdoor radio transmission systems. If space diversity with two vertically polarized antennas is not feasible due to lack of a second antenna mast, implicit polarization diversity will perform well, in particular if the imbalance of signal levels can be compensated e.g. by using a cross-polarized antenna with appropriately higher gain.

IEEE 802.15 Low Power Wide Area Network (LPWAN) PHY Interference Model - Robert, Jörg; Rauh, Sebastian; Lieske, Hendrik; Heuberger, Albert (2018 IEEE International Conference on Communications (ICC), 2018)
Low Power Wide Area Networks (LPWAN) are an interesting technology to provide wireless connectivity to low-power and low-cost devices over large distances in license exempt frequency bands. This goal is mainly achieved by very low payload bit-rates. However, the low rates result in long on-air times that make the LPWAN signals vulnerable to interference from other devices also operating in these frequency bands. This problem is especially relevant for LPWAN base-stations that are typically equipped with highly exposed antennas, resulting in high interferer signal levels. The IEEE 802.15 Interest Group Low Power Wide Area has therefore developed an interference model to analyze the impact of interferer signals on LPWAN transmissions. This paper presents the interference model as well as the underlying approach. Furthermore, it shows simulation results using the developed open source implementation of the interference model. These results highlight the relevance of interference in these networks.
Keywords: Interference; Antennas; Europe; Bandwidth; IEEE 802.15 Standard; Licenses; Receivers

Joint Time-Frequency Spectrum Usage Analysis and Modeling for the Shortwave - Rauh, Sebastian; Koch, Robert; Hedrich, Ewald; Robert, Jörg; Heuberger, Albert (Nordic conferences on HF communications, 2019)

Long-Term LPWAN Sub-GHz Deep Indoor-to-Outdoor Channel Model - Rauh, Sebastian; Lauterbach, Thomas; Robert, Jörg; Lieske, Hendrik; Kilian, Gerd; Heuberger, Albert (2019 IEEE 90th Vehicular Technology Conference (VTC2019-Fall), 2019)
Keywords: Channel Measurements; Channel Model; Indoor To Outdoor; Low Power Wide Area Networks; Narrowband and Wideband Channel Characterization and Modeling; Propagation Channel Measurements; Propagation Prediction and Simulation

LPWAN Occupancy Model Parameter Identification for License Exempt sub-GHz Frequency Bands - Rauh, Sebastian; Robert, Jörg; Schadhauser, Michael; Heuberger, Albert (German Microwave Conference (GeMiC), 2018)
For many applications Low Power Wide Area Net- works (LPWANs) are an appealing method to provide cost- efficient connectivity to many small and battery-driven devices spread over large areas. However, LPWANs are typically oper- ated in the license exempt sub-GHz frequency bands. This means they have to share the spectrum with other devices also operated in these bands, which can impair the LPWAN signals. In order to analyze the impact of interference on LPWAN signals the IEEE 802.15 Interest Group LPWA has defined an interference model that can be used for detailed Physical Layer (PHY) simulations. In order to define suitable parameter sets for this interference model we propose a processing framework based on image processing. This framework allows a broadband analysis of license exempt frequency bands. It is able to identify signal parameters such as access length, arrival rate, center frequency, and bandwidth. These obtained values can then be used as input parameters of the IEEE 802.15 interference model or other channel occupancy models. We present exemplary measurement results that we obtained during a field trial as part of the so- called Betriebs-Adaptive Tracking Sensorsysteme (BATS) project in Berlin, Germany and show the derived parameter sets.
Keywords: Occupancy Model; Interference Model; LPWAN; Image Processing

Multipath Characteristics of Indoor-to-Outdoor Radio Channels in the 868-MHz Band - Rauh, Sebastian; Lauterbach, Thomas; Lieske, Hendrik; Robert, Jörg; Heuberger, Albert (Conference Proceedings, 2016)
One of the major topics of machine-to-machine (M2M) communications are reliable data links in the license free ISM/SRD bands. To design such low power wide area (LPWA) systems which work in applications like smart metering, smart grid or Industry 4.0 a basic knowledge of the propagation channel characteristic of that bands is essential. With respect to findings from our previous works, the emphasis of this investigations is the frequency selectivity of propagation channels. Here we present the first results of field trials in urban and commercial area environments for the 868 MHz ISM/SRD band. To make multipath effects plausible for the frequency selectivity, we take the topographic conditions into account. Our findings show that a large number of propagation channels in the 868 MHz ISM/SRD band are affected by strong multipath fading and can classified in different categories. In this context the major multipath param- eters depend in a plausible way on the topographic conditions of environment. The temporal evolution of the parameters show strong correlation of successive days for propagation channels with mainly outdoor parts. In contrast, the multipath parameter for primarily indoor propagation channels show fluctuations over weekdays.
Keywords: Indoor-to-Outdoor; Multipath Propagation; ISM/SRD Bands

Numerical Evaluation of Information Outage for BPSK FHSS Link Performance Analysis - Lieske, Hendrik; Rauh, Sebastian; Heuberger, Albert (2017 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2017)
The information outage probability serves as a practical benchmark for the performance evaluation of channel codes in the finite block length region. The metric is derived from the distribution of the mutual information between a channel's in-and output and is readily available for the Gaussian AWGN channel. To review its applicability for modulation constraint channel inputs, we propose a numerical method for the evaluation of the mutual information random variable for BPSK modulated code words. We apply the model to a block fading channel to study the link performance of a frequency hopping spread spectrum (FHSS) system in a slow-fading two-path propagation environment, which is a typical scenario for low power wide area (LPWA) applications. The information outage probability closely reproduces the behavior of a practical rate 1/3 Turbo decoder.
Keywords: wireless sensor networks; information outage probability; BPSK; FHSS; channel coding; block fading channel

Occupancy Measurements of the Short-Wave Spectrum around 7.1 MHz over one Week - Rauh, Sebastian; Lieske, Hendrik; Koch, Robert; Hedrich, Ewald; Robert, Jörg; Heuberger, Albert (Conference Proceedings, 2016)
Due to time and location dependent propagation conditions, the occupancy of the short-wave spectrum is highly dynamic. To enable a reliable connection over the short-wave spectrum, Automatic Link Establishment (ALE) communication systems were developed in the past decades. Current systems typically rely on either MIL-STD-188-141 or STANAG 4538 standards and communicate over a finite set of channels, each with of 3 kHz bandwidth. As partially provided by the MIL-STD-188-110C standard, next generation short-wave communication systems adaptively allocate the utilized channel bandwidth. In order to provide data sets with realistic test scenarios for the performance evaluation of such systems, knowledge of the occupancy of the short-wave spectrum is required. For this reason, we performed spectrum measurements in Germany over one week. Here, the spectrum around 7.1 MHz was captured over a bandwidth of 500 kHz. To characterize the channel occupancy and statistical properties, such as individual occupancy lengths and their packet distance time, a signal processing chain was developed. We present our measurement setup and the subsequent signal processing chain. Furthermore, we provide first results on the time dependency of the channel occupancy as well as more detailed occupancy statistics.

Outage Probability and Base Station Coverage in Low Power Wide Area Networks - Lieske, Hendrik; Rauh, Sebastian; Robert, Jörg; Heuberger, Albert (2016 IEEE International Black Sea Conference on Communications and Networking (BlackSeaCom), 2016)
This paper presents an analytical model for the uplink performance analysis of low power wide area (LPWA) networks. Such networks typically serve for data aggregation in machine-to-machine (M2M) communication scenarios. Our model predicts the outage probability of desired radio nodes and is based on the inversion of the moment-generating function of a suitable defined random variable. Due to the peculiarities of LPWA networks, namely low access probabilities and static channel conditions, the numerical inversion is not a trivial task, and we propose the use of a special inversion algorithm to address this problem. The applicability of the proposed model is demonstrated for an exemplary network topology with a latency constraint. We obtain optimum medium access probabilities for either maximized network coverage area or a trade-off between coverage and power consumption.

Temporal Evolution Analysis of Indoor-to-Outdoor Radio Channels in the 868-MHz ISM/SRD Frequency Band - Rauh, Sebastian; Lauterbach, Thomas; Lieske, Hendrik; Kilian, Gerd; Robert, Jörg; Heuberger, Albert (European Microwave Conference, 2017)